Becoming Pan-European? : Transnational Media and the European Public Sphere - Brüggemann, Michael and Schulz-Forberg, Hagen (International Communication Gazette, 2009)
/ Research about the European public sphere has so far mainly focused on the analysis of national media, neglecting a dimension of transnational communication, namely transnational media. These media could serve as horizontal links between the still nationally segmented public spheres and they could be platforms of a transnational European discourse. Four ideal-types of transnational media can be distinguished: (1) national media with a transnational mission , (2) international media, (3) pan-regional media and (4) global media. Within this framework the article analyses transnational media in Europe, showing that a multitude of transnational media have developed in Europe. They have acquired a small but growing and influential audience. Whether transnational media fulfil the normative demands related to the concept of a transnational public sphere remains an open question as some of these media heavily depend on government subsidies and there is a clear lack of research on the European discourses represented in these media.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzQ4MDQ4NTA5MzQ1MDY0